Associations of Emergency Department Length of Stay With Publicly Reported Quality‐of‐care Measures. (February 2017) - Chang, Anna Marie; Lin, Amber; Fu, Rongwei; McConnell, K. John; Sun, Benjamin
Abstract: Objective: The Institute of Medicine identified emergency department (ED) crowding as a critical threat to patient safety. We assess the association between changes in publicly reported ED length of stay (LOS) and changes in quality‐of‐care measures in a national cohort of hospitals. Methods: Longitudinal analysis of 2012 and 2013 data from the American Hospital Association (AHA) Survey, Center for Medicare and Medicaid Services (CMS) Cost Reports, and CMS Hospital Compare. We included hospitals reporting Hospital Compare timeliness measure of LOS for admitted patients. We used AHA and CMS data to incorporate hospital predictors of interest. We used the method of first differences to test for relationships in the change over time between timeliness measures and six hospital‐level measures. Results: The cohort consisted of 2, 619 hospitals. Each additional hour of ED LOS was associated with a 0.7% decrease in proportion of patients giving a top satisfaction rating, a 0.7% decrease in proportion of patients who would "definitely recommend" the hospital, and a 6‐minute increase in time to pain management for long bone fracture (p < 0.01 for all). A 1‐hour increase in ED LOS is associated with a 44% increase in the odds of having an increase in left without being seen (95% confidence interval = 25% to 68%). ED LOS was not associated with hospital readmissions (p = 0.14) or time to percutaneous coronary intervention (p = 0.14). Conclusion: In this longitudinal study of hospitals across the United States, improvements in ED timeliness measures are associated with improvements in the patient experience.